The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/s0100-83582020380100001
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Potential of Some Dry Land Plants Against Lathyrus aphaca (L.), Winter Season Weed

Abstract: Dry land plants owing to their capability to grow under stressful environment have shown higher allelopathic potential as compared to cultivated plants. An experiment was conducted to investigate the herbicidal potential of aqueous extracts of four dry land plants viz. fruit and vine of Citrullus colocynthis, and above ground parts of Rhazya stricta; Crotalaria burhia and Calligonum polygonoides, with four concentrations (25, 50, 75 and 100%) of initially prepared extracts against Lathyrus aphaca, a common wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…No root elongation was observed at 35 and 50 g/L of Citrullus colocynthis. Also, in accordance with our results, Iqbal et al (2020) examine the herbicidal potential of aqueous extracts of Citrullus colocynthis fruit and vine at four concentrations (25, 50, 75, and 100%) against Lathyrus aphaca, a prevalent weed of wheat in the area under study. They mentioned that fruits and vines demonstrated strong herbicidal potential, suppressing several L. aphaca characteristics such as reduction in the number of leaves, shoot length, root length, shoot weight, root fresh weight, shoot dry weight, root dry weight, and nodule numbers.…”
Section: Response Of Amaranthus Retroflexus Seedling Root To Treatmen...supporting
confidence: 68%
See 1 more Smart Citation
“…No root elongation was observed at 35 and 50 g/L of Citrullus colocynthis. Also, in accordance with our results, Iqbal et al (2020) examine the herbicidal potential of aqueous extracts of Citrullus colocynthis fruit and vine at four concentrations (25, 50, 75, and 100%) against Lathyrus aphaca, a prevalent weed of wheat in the area under study. They mentioned that fruits and vines demonstrated strong herbicidal potential, suppressing several L. aphaca characteristics such as reduction in the number of leaves, shoot length, root length, shoot weight, root fresh weight, shoot dry weight, root dry weight, and nodule numbers.…”
Section: Response Of Amaranthus Retroflexus Seedling Root To Treatmen...supporting
confidence: 68%
“…Additionally, the inhibition of the shoot growth of Amaranthus retroflexus was observed at 35 and 50 g/L of Citrullus colocynthis. Also, Iqbal et al (2020) found that Citrullus colocynthis fruit and vine extracts at four concentrations (25, 50, 75, and 100%) had a strong effect in minimizing the growth of Lathyrus aphaca. They mentioned that fruits and vines demonstrated strong herbicidal potential, suppressing many of leaves, shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, and nodule numbers.…”
Section: 4mentioning
confidence: 96%
“…Based on the results of the experiment, it was determined that both substances had an allelopathic effect on the development of shoots from Zea mays seeds. Alkaloids, triterpenes, glycosides, tannins, and the volatile bases have all been found in the leaves of Lathyrus Aphaca L. specie [15].…”
Section: Plant Historymentioning
confidence: 99%
“…Allelopathy is the process in which a plant produces chemical substances (allelochemicals) that can interfere with the growth and establishment of other plants (Lovett & Ryuntyu, 1992;Li et al, 2011). In this context, biological control by allelopathy, can be an alternative in the control of exotic invasive species, favoring ecological restoration (Lopes, 2017;Iqbal et al, 2020). Allelochemical substances can bring an ecological and sustainable alternative for the control of exotic and invasive species such as bioherbicides (Rosa et al, 2007;Rigon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%